On the wealth and risk effects of commercial bank expansion into securities underwriting: An analysis of Section 20 subsidiaries - Bhargava, Rahul; Fraser, Donald R. (Journal of Banking & Finance, 1998)
We investigate the abnormal returns and market-based risk effects of four Federal Reserve Board decisions to allow bank holding companies to engage in investment banking through Section 20 subsidiaries. Positive abnormal returns for commercial banks were observed for initial, limited powers granted by the Federal Reserve. However, authorization to engage in underwriting corporate debt and equity and subsequent expansion of potential revenues from underwritings produced negative abnormal returns and increases in risk.